Empowering teachers with debate as a 21st-Century teaching strategy - Uci Elly Kholidah; Lina Purwaning Hartanti; Pratiwi Retnaningdyah; Widyastuti; Sueb; Layli Hidayah (University of Merdeka Malang, 2025)
This community engagement program was implemented to enhance critical and argumentative thinking skills through debate strategies at SMA SAIM Surabaya. The background of this initiative stems from the limited practice of structured debates and the lack of systematic integration of critical thinking in daily classroom activities. The primary objective was to enhance the capacity of both teachers and students to incorporate debate as a cross-curricular teaching method, applicable not only in language subjects but also in science, social studies, and physical education. The program was carried out through intensive training, direct practice via microteaching, reflection, and classroom mentoring. Evaluation was conducted both formatively and summatively, utilising daily reflections, logbooks, observations, and group discussions. The results showed a significant increase in teachers’ understanding of debate as a pedagogical strategy, their ability to design debate-based lesson scenarios, and the confidence of both teachers and students to engage in constructive argumentation. Over 90% of participating teachers reported an improvement in competence and the successful integration of debate into lesson planning. The program also produced training modules, assessment rubrics, and led to the establishment of a teacher learning community to support the sustainable integration of debate-based innovation in the school.